Looking at the past to infer into the future: Thermal traits track environmental change in Liolaemidae. (1st October 2021) - Ibargüengoytía, Nora Ruth; Medina, Marlin; Laspiur, Alejandro; Qu, Yan‐Fu; Peralta, César Augusto Ramirez; Sinervo, Barry; Miles, Donald B.
Abstract: The diversity of habitats generated by the Andes uplift resulted a mosaic of heterogeneous environments in South America for species to evolve a variety of ecological and physiological specializations. Species in the lizard family Liolaemidae occupy a myriad of habitats in the Andes. Here, we analyze the tempo and mode of evolution in the thermal biology of liolaemids. We assessed whether there is evidence of local adaptation (lability) or conservatism (stasis) in thermal traits. We tested the hypothesis that abiotic factors (e.g., geography, climate) rather than intrinsic factors (egg‐laying [oviparous] or live‐bearing [viviparous], substrate affinity) explain variation in field active body temperature (Tb ), preferred temperature (Tp ), hours of restriction of activity, and potential hours of activity. Although most traits exhibited high phylogenetic signal, we found variation in thermal biology was shaped by geography, climate, and ecological diversity. Ancestral character reconstruction showed shifts in Tb tracked environmental change in the past ∼20, 000 years. Thermal preference is 3°C higher than Tb, yet exhibited a lower rate of evolution than Tb and air temperature. Viviparous Liolaemus have lower Tb s than oviparous species, whereas Tp is high for both modes of reproduction, a key difference that results in a thermal buffer for viviparous species to cope with global warming. The rapid increase in environmental temperatures expected in the next 50–80 years in combination with anthropogenic loss of habitats are projected to cause extirpations and extinctions in oviparous species.